Motivasi Pengguna Warung Internet (Warnet) Dalam Kebutuhan Bermedia di Perkotaan - Suyanto ' (Universitas Riau, 2011)
Warnet is a container in accessing information through the intenet is issued and managed the localcommunity. Its presence is important in accelerating the achievement of the information society and medialiteracy to the dynamics of information, namely by making access to information, social interaction /communication through information technology facilities and communication technology (ICT) to thecommunity. This study aims to describe the motivation of users Warnet in meeting the needs of media forpeople in Pekanbaru. The results showed that the existence of Internet cafes to meet the needs of informationand communication is less optimally utilized in accordance with the objectives and targets, while meetingthe needs of entertainment considered quite high utilization.